On the applicability of the Flory–Huggins and Vrentas models for describing the sorption isotherms of wood. (2nd January 2017) - Hill, C.; Beck, G.
Abstract : This paper discusses the applicability of the Flory–Huggins and Vrentas sorption models for studying the sorption behaviour of wood. This theory was originally developed to explain the sorption behaviour of glassy polymers and was further extended to account for hysteresis effects. The model also has the advantage that, in principle, it does not require adjustable parameters for fitting and can be calculated independently of the sorption isotherm data. It was tested against some sorption isotherms and satisfactory fits to the data were obtained for both the absorption and desorption data. The values of the parameters required for satisfactory fitting were realistic, except for the magnitude of the glass transition temperature of water. As far as the authors are aware, this is the first reported study of the use of the Vrentas model to explain sorption and hysteresis in wood.